Effects of a Rehabilitation Program on Perceived Environmental Barriers in Older Patients Recovering from Hip Fracture: A Randomized Controlled Trial. (6th August 2013) - Portegijs, Erja; Rantakokko, Merja; Edgren, Johanna; Salpakoski, Anu; Heinonen, Ari; Arkela, Marja; Kallinen, Mauri; Rantanen, Taina; Sipilä, Sarianna
Abstract : Objectives . To study effects of a one-year multicomponent intervention on perceived environmental barriers in hip fracture patients. Design . Randomized controlled trial of a 12-month home-based rehabilitation aiming to improve mobility and function (ISRCTN53680197 ); secondary analyses. Subjects . Community-dwelling hip fracture patients on average 70 days after trauma (n = 81 ). Methods . Assessments at baseline, 3, 6, and 12 months later included perceived entrance-related barriers (e.g., indoor/outdoor stairs, lighting, floor surfaces, and storage for mobility devices) and perceived barriers in the outdoor environment (poor street condition, hilly terrain, long-distances, and lack of resting places). Sum scores for entrance-related and outdoor barriers were analyzed using general estimating equation models. Results . At baseline, 48% and 37% of the patients perceived at least one entrance-related barrier, and 62% and 60% perceived at least one outdoor barrier in the intervention and control group, respectively. Over time, (P = 0.003 ) the number of entrance-related barriers decreased in both groups (group P = 0.395 ; interaction P = 0.571 ). For outdoor barriers, time (P = 0.199 ), group (P = 0.911 ), and interaction effect (P = 0.430 ) were not significant. Conclusion . Our intervention had no additional benefit over standard care in hip fracture patients. Further study is warranted to determine whether perceived environmental barriers can be reduced by interventions targeted at the older individual. This trial is registered with ISRCTN53680197 .